Lysine (K)-specific methyltransferase 2A (KMT2A) rearrangements among Iraqi de novo acute myeloid leukemia - Riyam Qusay Al Jadir; Saba Abdulmahdi Abdulameer; Jaffar Nouri Alalsaidissa; Ali AlJabban (Iraqi Journal of Hematology)
BACKGROUND: The classification of acute myeloid leukemia (AML) has evolved extensively over the last 20 years significantly, impacting the diagnosis and prognosis of the patients. The lysine (K)-specific methyltransferase 2A (KMT2A) gene, which has more than 80 gene fusions, is present in approximately 10% of all leukemias. Most KMT2A rearrangements are associated with adverse prognosis and need heavy chemotherapy protocol upfront. OBJECTIVE: This study aims to study the prevalence of KMT2A gene fusion among Iraqi patients with AML and its association with clinical and hematological parameters and patients’ outcomes. PATIENTS, MATERIALS, AND METHODS: A prospective cohort study conducted between December 2020 and May 2022 enrolled 115 Iraqi adults newly diagnosed with AML at the Hematology Unit of Baghdad Teaching Hospital. The patients were also monitored at this facility during the study period. Genetic rearrangements were detected using the Leukemia Q-Fusion Screening Kit through Real-Time Quantitative Reverse Transcription PCR (RT-qPCR) analysis. RESULTS: KMT2A rearrangements were identified in 23 (20%) patients. The most common was t(10;11) which presented in 15 (13%) patients, followed by t(9;11) in 5 (4.3%) patients and t(11;17) in 3 (2.6%) patients. Patients with KMT2A rearrangements were significantly older and more likely to have splenomegaly. At 1-month posttreatment, they had significantly lower red blood cell counts and hemoglobin levels and higher blast percentages. Only 4.3% achieved complete remission (CR) compared to 76.1% without KMT2A rearrangements, with a significantly higher mortality rate (30.4% vs. 5.4%, P = 0.0001). Regarding the treatment response, no significant differences were observed among the different fusion types of KMT2A rearrangements. CONCLUSION: KMT2A rearrangements are more prevalent among Iraqi AML patients compared to the global trend and are associated with older age, higher rates of splenomegaly, poorer hematological recovery, and worse outcomes, regardless of the KMT2A rearrangement fusion type.